Factores intra y extralaborales de los y las trabajadoras de una empresa pública de Costa Rica. - Sánchez Charpentier, Olga (2009)
The following article presents the results of research comparing the factors inside and outside work for workers in a public company in Costa Rica. This work was conducted during 2005. We designed a qualitative study using the structural method action research. The population consisted of 12 men and 12 women, employees of a public company. The information was collected through focus group technique as it allows to understand the factors that affect the work process, also used a structured questionnaire to collect data related to socio-demographic conditions of the population. At the same time, the Index Cornell was used to find if the population had symptoms related to stress. In conclusion, we find that people living with intralaboral factors such as lack of recognition in their work and gender inequality, in terms of outside work, family concerns of care and family care are barriers to run with satisfaction their work. For these reasons, an improvement of these conditions will favor the production and reproduction of the workforce.